Peer Victimization: Hitting Psychological Distress, Self Esteem and Psychological Well-being among Adolescents - Khizar, Umbreen; Liaquat, Sidra; Jahangir, Nazia (International Journal of Engineering and Technology, 2018)
Children have to face a lot of problems related to their academics, coping with society, peer relations, bulling and victimization. Research has reported increasing rate of bulling at school and colleges in Pakistan. Bullying is a public health problem and has serious negative impacts for the bully and for the victim, causing serious social and personal problems. This research was aimed to explore the relational aspects of bullying in form of peer victimization, psychological distress and self-esteem among adolescence. Sample was consisted of 200 students; their age varies from 10-17 years from different institutes of Multan. Bully Scale [1] subscale peer victimization was used in this study. Psychological Distress Scale [2], State Self-esteem Scale [3] and Psychological Well-being Scale [4] were used. Results suggested that being victimized by peers is significantly related to high levels of psychological distress, low self-esteem and psychological wellbeing. Findings indicated that distress is high among peer victims of bullying as compare of bullies. Significant gender differences were found. This research suggests that bulling prevention trainings, workshops and seminars must be part of school education. Parents need to be aware of bullying attitudes and have concern for wellbeing and self-esteem.